If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -5(3 + -8y) = 0 15 + (3 * -5 + -8y * -5) = 0 15 + (-15 + 40y) = 0 Combine like terms: 15 + -15 = 0 0 + 40y = 0 40y = 0 Solving 40y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '40'. y = 0.0 Simplifying y = 0.0
| -7(1+5x)+3=-8(4x+5) | | y=6sin(6x) | | 9(a-3)+2= | | 3.5x-20=2.4x-13 | | -x-x^2=14 | | 2x+4y=76 | | -7x+1=-12x-12 | | -5(1-5k)+5(-8k-2)=-4k-8k | | 12x-3=13x-1 | | 8y=2x | | 100-x=-81 | | 7+q-7q-6q+3= | | 6a-17=4a+1 | | -7(2n-6)=7(n+3) | | 8=z-7 | | 3+9z-8h= | | 7x-8=3(x+2) | | 15x-9x=48 | | 8b-a=-3 | | 4(3d-2)=32 | | x^2+2x-52=0 | | -6(5+3x)=14 | | cos(6x)=cos(4x) | | 14.2=0.4(20m-7.8) | | 24+9=21 | | 24+9= | | a+4b=6 | | 12(2e+3)=96 | | -4z-5=8z+3 | | C=20n+8 | | (2z+9)(7-z)=0 | | f(x)=-8x^2+8x+9 |